The Value of TTPVI in Prediction of Microvascular Invasion in Hepatocellular Carcinoma - Zhang T; Pandey G; Xu L; Chen W; Gu L; Wu Y; Chen X (Cancer Management and Research, 2020)
Tao Zhang,1,* Gaurab Pandey,1,* Lin Xu,1 Wen Chen,1 Liangrui Gu,1 Yijun Wu,1 Xiuwen Chen2 1Department of Radiology, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, People’s Republic of China; 2Department of Pathology, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lin Xu Email linxu850@gmail.comPurpose: The objective of our study was to evaluate the value of two-trait predictor of venous invasion (TTPVI) in the prediction of pathological microvascular invasion (pMVI) in patients with hepatocellular carcinoma (HCC) from preoperative computed tomography (CT) and magnetic resonance (MR).Methods: A total of 128 preoperative patients with findings of HCC were enrolled. Tumor size, tumor margins, tumor capsule, peritumoral enhancement, and TTPVI was assessed on preoperative CT and MRI images. Histopathological features were reviewed: pathological tumor size, tumor differentiation, pMVI along with alpha-fetoprotein level (AFP). Significant imaging findings and histopathological features were determined with univariate and multivariate logistic regression analysis.Results: Univariate analysis revealed that tumor size (p< 0.01), AFP level (p=0.043), tumor differentiation (p< 0.01), peritumoral enhancement (p=0.003), pathological tumor size (p< 0.01), tumor margins (p< 0.01) on CT and MRI, and TTPVI (p< 0.01) showed statistically significant associations with pMVI. In multivariate logistic regression analysis, tumor size (odds ratio [OR] = 1.294; 95% confidence interval [CI]: 1.155, 1.451; p < 0.001), tumor differentiation (odds ratio [OR] =1.384; 95% confidence interval [CI]: 1.224, 1.564; p < 0.001), and TTPVI (odds ratio [OR] = 4.802; 95% confidence interval [CI]: 1.037, 22.233; p=0.045) were significant independent predictors of pMVI. Using 5.8 as the threshold for size, one could obtain an area-under-curve (AUC) of 0.793, 95% confidence interval [CI]: 0.715 to 0.857.Conclusion: Tumor size, tumor differentiation, and TTPVI depicted in preoperative CT and MRI had a statistically significant correlation with pMVI. Hence, TTPVI detected on CT and MRI may be predictive of pMVI in HCC cases.Keywords: CT, MRI, hepatocellular carcinoma, microvascular invasion, two-trait predictor of venous invasion